2021
DOI: 10.3389/fvets.2021.682330
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Seven Measures to Reduce Tail Biting Lesions in Fattening Pigs

Abstract: Tail biting is an important animal welfare issue in the pig sector. Studies have identified various risk factors which can lead to biting incidents and proposed mitigation measures. This study focused on the following seven key measures which have been identified to affect the risk of tail biting lesions: improvements in straw provision, housing ventilation, genetics, stocking density, herd health, provision of point-source enrichment objects, and adoption of early warning systems. The aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 79 publications
(141 reference statements)
5
12
0
Order By: Relevance
“…Regarding the profitability requirements, our results are in agreement with the recent study concerning the cost-effectiveness analysis of measures to reduce tail biting in fattening pigs [ 43 ]. According to Niemi et al [ 43 ] interventions which were considered the least expensive to apply (e.g. such as provision of point-source enrichment objects) or provided wider production benefits (e.g.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Regarding the profitability requirements, our results are in agreement with the recent study concerning the cost-effectiveness analysis of measures to reduce tail biting in fattening pigs [ 43 ]. According to Niemi et al [ 43 ] interventions which were considered the least expensive to apply (e.g. such as provision of point-source enrichment objects) or provided wider production benefits (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding management interventions, our results indicated that the provision of point-source objects is financially viable for reducing perinatal mortality. Similar results were obtained in a previous study on cost-effective measures to reduce tail-biting in fattening pigs [ 43 ], mostly due to the relatively low prices of intervention. Even though, in our study, enrichment consisted of both high-fiber diet and provision of wood attached to a chain, the measure was quite inexpensive to be adopted across different production conditions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…On a farm with 10% prevalence of tail injuries, costs were estimated to be EUR 2.30 and on a farm with 50% prevalence more than EUR 12. For most of the expensive measures (as straw provision), therefore, a large effect (reduction in prevalence of injuries) is required to be profitable [ 82 ].…”
Section: Discussionmentioning
confidence: 99%